IMPLEMENTASI METODE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR IPS PESERTA DIDIK KELAS 5 SD NEGERI INDRO KEBOMAS GRESIK - Iddho Chafidho; Ismail Marzuki (JUSEDA, 2020)
This study aims to improve students' social studies learning outcomes through mind mapping learning methods in grade 5 of SD Negeri Indro Kebomas Gresik. This type of research is classroom action research that will examine the activities of teachers and students in the teaching and learning process. The research subjects were 31 students in the 5th grade of SD Negeri Indro Kebomas Gresik, with data collection techniques through observation and tests. After the data has been collected, the data is then analyzed and determined the percentage level and performance criteria. This research was conducted in 2 cycles with 5 meetings and the result was an increase in the percentage and achievement of teacher activity criteria, student activities, also includes learning outcomes. In the first cycle the teacher's activity reached 89% with very good criteria, while the activities of students 79% with good criteria, and 77.4% learning outcomes which also means that indicators have not yet been reached. After making improvements in the second cycle the teacher's activity became 97% with very good criteria, student activity obtains 84.6% very good criteria, and the learning outcomes are 90.3%.